1991
DOI: 10.1073/pnas.88.9.3962
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of large rRNAs by RNA polymerase II in mutants of Saccharomyces cerevisiae defective in RNA polymerase I.

Abstract: The 35S rRNA gene of the yeast Saccharomyces cerevisiae was fused to the GAL7 promoter. This hybrid gene, when present on a multicopy plasmid and induced by galactose, suppressed the growth defects of a temperaturesensitive RNA polymerase I (pol I) mutant and those of a mutant in which the gene for the second largest subunit of pol I was deleted. Analysis of pulse-labeled RNA directly demonstrated that rRNA synthesis in this deletion mutant is from the GAL7 promoter. These experiments show that the sole essent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
162
1
1

Year Published

1991
1991
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(166 citation statements)
references
References 34 publications
2
162
1
1
Order By: Relevance
“…Possibly any nuclear RNA with appropriate rRNA processing signals can be matured into 18S, 5.8S, and 25S rRNA. Indeed, it has been shown that rRNA transcribed from a GAL1 Pol II promoter construct is still able to produce functional rRNA (30). (28).…”
Section: Resultsmentioning
confidence: 99%
“…Possibly any nuclear RNA with appropriate rRNA processing signals can be matured into 18S, 5.8S, and 25S rRNA. Indeed, it has been shown that rRNA transcribed from a GAL1 Pol II promoter construct is still able to produce functional rRNA (30). (28).…”
Section: Resultsmentioning
confidence: 99%
“…When the intron sequences were cloned into a yeast plasmid expressing the full-length 35S pre-rRNA from the GAL7 promoter ( Fig. 1A; Nogi et al 1991), we again observed little unspliced pre-rRNA on Northern blots (Fig. 1B).…”
Section: In Vivo Splicing Is Linked To Rrnamentioning
confidence: 99%
“…Full-length 35S pre-rRNA was expressed from pNOY102, which contains the GAL7 promoter fused to a single copy of the 35S rRNA operon (6922 bp) from S. cerevisiae (Nogi et al 1991) and was the gift from M. Nomura. pNOY102-Tag was the gift of B. Peculis and contains a unique 18-nt sequence tag in the 59 end of the 25S rRNA (Peculis and Greer 1998).…”
Section: Plasmid Constructionmentioning
confidence: 99%
“…Yeast A135 harboring mutation that abolishes A135 interaction with AC40/AC19 in two-hybrid system is functional. Yeast tester strain NOY308 -1a, which lacks A135 and is kept viable by the presence of Gal7-rDNA plasmid (26), was transformed with vector plasmid or plasmids expressing wild-type A135, or mutant A135 with D935A substitution. Transformants were spotted on rich medium containing galactose (top row) or glucose (bottom row) as carbon source.…”
Section: Discussionmentioning
confidence: 99%
“…To test the functional consequence of D935A substitution in A135, which abolishes the A135-AC19/AC40 interaction in the two hybrid assay, yeast plasmid expressing the mutant A135 gene was constructed. The phenotype of this gene was tested using haploid NOY408 -1a yeast tester strain (26). In this strain the chromosomal copy of A135 has been deleted, and the cells are kept viable because of the presence of a multicopy plasmid harboring an rDNA repeat under the control of GAL7 (RNAP II) promoter.…”
Section: Fig 2 a Strong Intrasubunit Interaction Between ␤ Segmentsmentioning
confidence: 99%